Complete chloroplast genome and phylogenetic analysis of a wild grass, Hordeum roshevitzii Bowden. Issue 3 (4th March 2021) - Zhang, Ruochen; Li, Xiuzhang; Chen, Zhenjiang; Yao, Xiang; Li, Tao; Li, Chunjie
Abstract: The complete circular chloroplast (cp) genome of wild Hordeum roshevitzii Bowden was sequenced and reported in this study. The complete chloroplast genome of wild H. roshevitzii was 12, 753 bp in length, including a pair of inverted repeat regions (IRA/IRB) of 21, 587 bp separated by one small single-copy (SSC) region of 12, 753 bp and one large single-copy (LSC) region of 81, 138 bp. A total of 133 genes, including 85 protein-coding genes (PCGs), 40 transfer RNA genes, and 8 ribosomal RNA genes were predicted from the cp genomes. The overall GC content of the cp genome was 38.25% and the corresponding values of the IR, SSC, and LSC were 43.89%, 32.19%, and 36.21%. The phylogenetic analysis of H. roshevitzii determined that H. roshevitzii was clustered closely with Hordeum bogdanii.